Integrasi Pendidikan Kejuruan dalam Kebijakan Hukum Keimigrasian untuk Mewujutkan Tenaga Kerja Unggul di Era Generasi Emas Tahun 2045 - Alkatiri, Ammar abdu Jawad; Maidah Purwanti; Sohirin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Immigration law enforcement has undergone significant developments in line with social, political, and technological changes. In the era of the Golden Generation 2045, new challenges arise along with demographic changes and increasingly complex global dynamics. This paper examines how immigration law enforcement and oversight are evolving by analyzing changes and the impact of technological developments, economic growth, the environment, and long-term approaches to improving law enforcement efficiency. It also explores efforts to achieve a balance between firm law enforcement and policies that respect human rights, and their impact on immigration law enforcement. This article aims to provide insight into the role of immigration law enforcement in the era of the Golden Generation 2045 and its implications for an increasingly connected global society.